A demographic profile of the Cape metropolitan area, 1996 and 2021 - Haldenwang, Bärbel (University of the Free State, 2001)
With a total population of 2.56 million in 1996, the Cape Metropolitan Area (CMA) is the third largest metropole in South Africa. It is the second largest contributor to the country’s GDP, accounts for 8.0% of employment, and is a popular migration destination, especially from the Eastern Cape. The population of the CMA is demographically young, with more females than males, and it is dominated by the coloured population group. Each of the six local authority areas has its own unique demographic profile. By 2021, between 0.76 million and 1.56 million additional people could be residing in the CMA, with Tygerberg and Central Cape Town expected to experience the highest population growth rates.

Met ’n bevolking van 2.56 miljoen in 1996 is die Kaapse Metropolitaanse Gebied (KMG) die derde grootste metropool in Suid-Afrika. Die KMG is voorts die tweede grootste bydraer tot die land se BBP, is verantwoordelik vir 8% van werkverskaffing in Suid-Afrika en is ’n gewilde migrasiebestemming, veral vir migrante uit die Ooskaap. Die bevolking van die KMG is demografies jonk met meer vrouens as mans en gedomineer deur die Kleurlingbevolkingsgroep. Elk van die ses plaaslike owerheidsgebiede in die KMG het ’n unieke demografiese profiel. Teen 2021 sal die KMG na verwagting tussen 0.76 miljoen en 1.56 miljoen addisionele inwoners hê. Tygerberg en Sentraal-Kaapstad sal waarskynlik die vinnigste bevolkingsgroei ervaar.
Keywords: Cape Metropolitan Area; Employment; Demographic profile